PENGEMBANGAN APLIKASI ANDROID INTERAKTIF BERBASIS MULTIMEDIA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR ANAK USIA DINI DI KELOMPOK BELAJAR KARTINI PEKON PASIR UKIR - Edi Nofiyanto; Suyono Suyono (JECE (Journal of Ethics and Character Education), 2026)
This study aimed to develop and evaluate an interactive multimedia-based Android application, namely PAUDITA (PAUD Interaktif Tanpa Batas), to improve learning motivation and learning outcomes among early childhood learners at Kartini Learning Group, Pasir Ukir Village. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observations, interviews, questionnaires, documentation, and pretest-posttest assessments. The developed application integrates interactive learning materials, educational videos, audio-supported instructions, word-building activities, and automated assessment features. Validation results from experts indicated a high level of feasibility with an average score of 94.0%. Teacher responses demonstrated excellent practicality with a score of 94.2%, while students’ learning motivation reached 92.8%. Furthermore, learning outcomes improved significantly, with the average score increasing from 61.50 in the pretest to 86.75 in the posttest, resulting in an N-Gain score of 0.66. These findings indicate that the PAUDITA application is valid, practical, and effective in enhancing motivation and learning achievement among early childhood learners through interactive mobile learning.